1998
DOI: 10.1046/j.1365-2141.1998.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐endothelial cell antibodies in primary antiphospholipid syndrome and SLE: patterns of reactivity with membrane antigens on microvascular and umbilical venous cell membranes

Abstract: Although there has been recent emphasis on autoantibodies to epitopes on beta-2-glycoprotein I and prothrombin in the pathogenesis of antiphospholipid syndrome (APS), antibodies other than those directed toward epitopes on phospholipid binding proteins are present. These include those reactive with antigens on platelet membrane glycoproteins, and with vascular endothelial cell membrane. As the pathogenesis of the thrombotic manifestations of APS remains unexplained, further characterization of these antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…Hill et al [28] reported anti-endothelial cell binding to a range of cell membrane antigens in SLE and primary anti-phospholipid syndrome, and also reported dierences in both the pattern of antibody binding and band intensity between HUVEC and HMEC-1. These results are consistent with the phenotypic variation in endothelial cells of dierent origins, and con®rm the frequent presence of autoantibodies reactive with vascular endothelium in both SLE and primary antiphospholipid syndrome.…”
Section: Discussionmentioning
confidence: 96%
“…Hill et al [28] reported anti-endothelial cell binding to a range of cell membrane antigens in SLE and primary anti-phospholipid syndrome, and also reported dierences in both the pattern of antibody binding and band intensity between HUVEC and HMEC-1. These results are consistent with the phenotypic variation in endothelial cells of dierent origins, and con®rm the frequent presence of autoantibodies reactive with vascular endothelium in both SLE and primary antiphospholipid syndrome.…”
Section: Discussionmentioning
confidence: 96%
“…However, the ACA were not accompanied by antibodies reactive with the vascular endothelium (AECA). This situation is distinct from that in APS, where antiendothelial cell reactivity is also detectable in over 50% of cases [15, 16]. The relationship between antibodies reactive with negatively charged phospholipids and thrombosis has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Anticardiolipin antibody (ACA), an APA, has been reported to be present in increased titre in the serum of 5–9% of patients with retinal vascular occlusions, both arterial and venous [10, 11, 12, 13, 14]. In primary and secondary (associated with another auto-immune disease) APS, antibody reactivity with vascular endothelial cell membrane (antiendothelial cell antibody, AECA) is also a frequent finding and may contribute to the pathogenesis [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…True AECA directed against constitutive endothelial antigens and distinct from anti-␤ 2 GPI antibodies have also been found in the sera of patients with both APS and SLE-associated APS (40,44).…”
Section: Disease Association and Prevalence Of Aecamentioning
confidence: 99%
“…A recent analysis of AECA specificity in primary APS and SLE revealed differences in both the pattern of antibody binding and band intensity between membrane antigens on HUVEC and those on human microvascular EC (44). In fact, of 17 primary APS sera, antibody binding to HUVEC membranes was found in 9 sera and to human microvascular EC membranes in 7 sera.…”
Section: Classification Of Aeca As Antibodies Against Microvascular Amentioning
confidence: 99%